Feminism through hip-hop: a case study of "Hal" by Arabyrd, Sophia Liana, Hullera and DJ Ziqq & "Rani Cypher" by Raja Kumari feat. Siri, Meba Ofilia and Dee MC / Ruvianatasya Ruslan - Ruslan, Ruvianatasya (2022)
This research aims to discuss the efforts of feminist musicians to promote female empowerment and gender equality in rap music. The objective of this research is to identify existing feminism elements and to analyze the major feminism elements. To do so, is by apply the thematic analysis method to quantifying qualitative research.